Resilience Strategy of Indonesian Seafarers in Facing Pressure and Stress on Ships - Alfian, Andi; Iskandar, Abdul Malik; Jalal; Hasanuddin (CV. Eureka Murakabi Abadi, 2024)
This study aimed to describe the resilience strategies used by Indonesian sailors in dealing with pressure and stress on board. This type of research used qualitative descriptive research with the determination of informants consisting of 7 informants selected using purposive sampling techniques. Data collection techniques used were observation, interviews, and documentation. The results of the study indicate that there are several resilience strategies used by Indonesian sailors in dealing with pressure and stress on board, including a) Cognitive strategies are managing feelings of stress and longing through positive thinking patterns, effective communication, and focusing on goals and the future of the family; b) emotional strategies are to combine social support, emotional management, spirituality amid tough work challenges and isolation situations at sea; c) social strategies are by building solid relationships, open communication, and emotional support from coworkers; d) professional strategies are by combining increased competence, discipline, self-management, and adaptability.